2020
DOI: 10.1101/2020.05.15.20103226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Access to primary healthcare during lockdown measures for COVID-19 in rural South Africa: a longitudinal cohort study

Abstract: Objectives Public health interventions designed to interrupt COVID-19 transmission could have deleterious impacts on primary healthcare access. We sought to identify whether implementation of the nationwide lockdown (shelter-in-place) order in South Africa affected ambulatory clinic visitation in rural Kwa-Zulu Natal (KZN). Design Prospective, longitudinal cohort study Setting Data were analyzed from the Africa Health Research Institute Health and Demographic Surveillance System, which includes prospective d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 31 publications
(46 reference statements)
6
54
2
Order By: Relevance
“…However, these findings are new and bear potential significant implications. Local health workers anecdotally reported they had the feeling that people could not afford routine care (from transport fees to visit fees for those over 5 years of age), and our data provide, to the best of our knowledge, the first evidence of a possible drop in access for basic but priority pediatric services in remote areas, while similar rates have already been reported in the adult population of South Africa (6). A similar scenario is currently happening in the United States, where a recent nationwide analysis of vaccine information found that measles, mumps, and rubella vaccinations had dropped by 50% during the COVID-19 outbreak (6).…”
Section: Discussionsupporting
confidence: 71%
“…However, these findings are new and bear potential significant implications. Local health workers anecdotally reported they had the feeling that people could not afford routine care (from transport fees to visit fees for those over 5 years of age), and our data provide, to the best of our knowledge, the first evidence of a possible drop in access for basic but priority pediatric services in remote areas, while similar rates have already been reported in the adult population of South Africa (6). A similar scenario is currently happening in the United States, where a recent nationwide analysis of vaccine information found that measles, mumps, and rubella vaccinations had dropped by 50% during the COVID-19 outbreak (6).…”
Section: Discussionsupporting
confidence: 71%
“…Besides the potential impact of COVID-19 on fetal-maternal health, the emergence of a new and highly contagious virus, including the unprecedented containment and social isolation measures, might have created (exceptional) challenges for perinatal and child healthcare [15]. In Belgium, it is common practice for pregnant women to consult with several types of health care professionals (HCPs) throughout their pregnancy (i.e., obstetrician, midwife, general practitioner (GP) or medical specialist).…”
Section: Introductionmentioning
confidence: 99%
“…Our experience of working during this time has been of increased challenges and adversity associated with logistical, resource, and sta ng di culties. Interestingly, a study of the effects of Covid-19 lockdown measures on access to primary care in rural South Africa had similar unexpected results (20).…”
Section: Discussionmentioning
confidence: 88%